Design and Implementation of Global Flight Tracking System Based on Space-Based Network - Bin LUO; Junjie CHEN; Kai CUI (天地一体化信息网络)
Based on the analysis of the application scenarios and requirements of the global fl ight tracking of space-based network, aim at the application characteristics of the satellite network in the field of civil aviation, the overall system and subsystem preliminary design, key technology analysis, business focus and difficulty analysis were carried out, the global flight tracking prototype system construction and test verifi cation was completed.The results showed that the system is stable and reliable, the fl ight path is complete, and meets the requirements of 4D/15 fl ight tracking and surveillance.The future application in the industry will play an important role in improving the aviation security system, and ensuring the information and data security of civil aviation.